Healthcare Workers Attitude and Stigma among People living withHIV/AIDS (PLHA): A Literature Review - Janet Alexis De los Santos (San Beda University, 2020)
Background: The concept of stigma and discrimination discussed in literature illuminate patient's experiences in the hands of health care providers. The review aims to assess the existing literature published in internet databases focusing on the personal perception of stigma and discrimination of health care workers as well as the patient's perception of their attitudes that may be stigmatizing and discriminatory. Methodology: A web-based search was done in the three (3) databases including EBSCOhost, Google Scholar, and PubMed. The search utilized five keywords: 'Stigma'; 'Discrimination', 'Perception', HIV/AIDS,' and 'Nurses.' Inclusion criteria includes full-text, peer-reviewed, academic journal in the English language, and published between the years 2013-2018. The studies were screened according to their relevance to the objectives of the study. The quantitative and qualitative checklist of the Standard Quality Assessment Criteria for Evaluating Primary Research Papers and Joanna Briggs Institute data extraction protocols were utilized by two interrater in the analysis of the literature. The extracted data were synthesized using a table highlighting the key findings of the studies. Results: A total of fourteen (14) titles were included in the review after evaluating its relevance to the objective and appraising its high quality. Content analysis was done and resulted in the formulation of four themes which include: (1) General Characteristics of the Literature (2) HIV/AIDS Stigma and Discrimination as perceived by health care providers; (3) Perception of health providers' attitude among HIV infected persons; and, (4) the consequences of HIV/AIDS stigma. Conclusion: The issue of HIV/AIDS stigma and discrimination is a significant component that affects patient - care provider interaction. Health care providers understand the role they play in improving the lives of their PLHA patients. Likewise, patients perceive that stigma is existent and tangible in health care facilities. HIV/AIDS stigma is a barrier between the patient and the health care team and can lead to the detriment of the patient's health outcomes and satisfaction.